(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Road transport plays a vital role in any country not only in meeting transport requirements, but also in economic growth. It offers both time and location. In a country like India, the bulk of the population from semi-urban and rural areas depends mostly on road transportation for their daily commute. Maharashtra State Road Transport Corporation (MSRTC) is India’s third largest state transport company with greatest fleet size, representing 7.3 of the state-owned road transport undertakings (SRTUs)’ total fleet size (SFRTUs) (2015-16). Its goal is to offer state-wide free and safe bus services. It is a convenient and inexpensive way to convey remote parts of the State through various category services, such as ordinary and luxurious services. Though MSRTC’s financial performance was not adequate, and subsequently saw enormous losses in recent decades, it is nevertheless willing to fulfill its motto ’where a road is there, the bus service is available.’ This article analyses the challenges and obstacles experienced over many years by Maharashtra State Road Transport Corporation (MSRTC). The policymakers of state transport firms, academics and experts a lot of useful results and consequences.